2001
DOI: 10.1163/15685590160141341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum E-cadherin levels in patients with haematological malignancies

Abstract: E-cadherin is a transmembrane glycoprotein that mediates Ca2+-dependent intracellular adhesion in normal epithelial cells. E-cadherin levels in serum are known to be significantly elevated in patients with epithelial carcinomas. However, the role of E-cadherin in haematopoietic cells is less clear. In this study, serum E-cadherin levels were therefore determined in patients with acute or chronic leukaemia, malignant lymphoma or myelodysplastic syndromes. Significant elevation of serum E-cadherin levels was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…An important finding is that serum sE-cadherin in blast crisis of CML is higher than in the chronic phase. 34 Another study observed similar findings in a cohort of MDS patients: elevated serum sE-cadherin correlates with poor prognosis. 30 Moreover, in newly diagnosed multiple myeloma (MM), high serum sE-cadherin levels (~six-fold) were observed compared to healthy controls and correlated with lactate dehydrogenase (LDH) levels, a non-specific tumor serum marker that was found as an independent prognosis factor of survival.…”
Section: Hematological Malignanciesmentioning
confidence: 63%
See 1 more Smart Citation
“…An important finding is that serum sE-cadherin in blast crisis of CML is higher than in the chronic phase. 34 Another study observed similar findings in a cohort of MDS patients: elevated serum sE-cadherin correlates with poor prognosis. 30 Moreover, in newly diagnosed multiple myeloma (MM), high serum sE-cadherin levels (~six-fold) were observed compared to healthy controls and correlated with lactate dehydrogenase (LDH) levels, a non-specific tumor serum marker that was found as an independent prognosis factor of survival.…”
Section: Hematological Malignanciesmentioning
confidence: 63%
“…19 Moreover, the soluble forms of some of these surface markers increase in the serum of patients with hematological malignancies, such as leukemia. [29][30][31][32][33][34] As the source of the soluble forms are the membrane-bound proteins, one question can be raised: can the serum levels of soluble forms be correlated with the surface protein expression on the leukemic cells? In this review, we highlighted the role of these four adhesion molecules in carcinomas and hematological malignancies, mainly leukemia, and discuss evidence about this matter.…”
Section: Introductionmentioning
confidence: 99%
“…E-cadherin is one of soluble adhesion molecules such as E-selectin. We have reported that serum E-cadherin levels in patients with various haematologic malignancies were signi cantly elevated when compared to healthy adult volunteers, and therefore serum E-cadherin level might be a diagnostic value in patients with haematologic malignancies [11]. We suspect that E-cadherin protein might be produced in haematopoietic cells and be associated with progression, proliferation and in ltration of malignant haematopoietic cells of some haematologic malignancies.…”
mentioning
confidence: 96%
“…Os valores das concentrações séricas de sCD44 e sE-caderina encontrados neste estudo foram menores do que os relatados na literatura, tanto em pacientes com LLA em remissão, quanto em controles saudáveis (TAKEUCHI et al, 1999;TAKUBO et al, 2002), o que pode ser explicado pelas diferenças nas técnicas de diluição e quantificação das amostras. As concentrações séricas de sEpCAM foram determinadas em unidades de medida (UI/mL) diferentes das utilizadas em outros estudos (ng/mL) (GEBAUER et al, 2014;MARTOWICZ;KARABULUT;DURANYILDIZ, 2014), estabelecidas de acordo com os fabricantes dos respectivos kits de quantificação, dificultando a comparação dos valores das concentrações séricas encontradas com os publicados na literatura.…”
Section: Discussionunclassified
“…Níveis séricos de sCD44 e sE-caderina são elevados em pacientes com várias doenças malignas hematológicas, incluindo leucemias pediátricas, em comparação com indivíduos saudá-veis (AMIRGHOFRAN et al, 2016;KHAN et al, 2008;TACYILDIZ et al, 2001;TAKEUCHI et al, 1999;TAKUBO et al, 2002).…”
Section: (Figura 3)unclassified